Sex Disparities in the Presentation of Gallbladder Disease. Issue 2 (February 2022) - Bailey, Kimberly S.; Marsh, Wallis; Daughtery, Levi; Hobbs, Gerry; Borgstrom, David
Introduction: Although gallbladder disease is more common in women, there is a trend toward more complicated cases in male patients. Methods: All cholecystectomies captured by the National Surgical Quality Improvement Program database for the year 2016 were reviewed. This encompassed 38 736 records. Records were reviewed for age, sex, procedure performed, operative time, postoperative diagnosis, functional status, American Society of Anesthesiologists (ASA) class, preoperative lab values (total bilirubin, alkaline phosphatase, white blood cell count, and aspartate aminotransferase. Descriptive and inferential statistical analyses were conducted. Results: Male patients are more likely to undergo cholecystectomy for a diagnosis of cholecystitis, gallstone pancreatitis, or cholangitis than women who are more likely to carry a diagnosis of biliary dyskinesia. The average operative time increases for both sexes as the patients become older. The average operative time is higher for men than women in all age groups and the variance becomes greater as the patients become older. Age, sex, postoperative diagnosis, ASA class, and functional status were all independently significant in predicting operative time. There was no difference in need for cholangiogram between the sexes. Female patients were more likely to have their cholecystectomy completed laparoscopically and they were more likely to have their surgery performed as an outpatient. Conclusion: These data show that women were more likely to present with uncomplicated gallbladder disease, while men were more likely to present with complicated gallbladder disease. This suggests that male patients present at a more advanced stage of disease.